Challenges for Interdisciplinary Use in Forest Management Prompts of Coalition of Forest Management, Economic and Institutional Sciences: 2005, 361 pages - Hariadi Kartodihardjo (Institut Pertanian Bogor (IPB University), 2013)
In general, the science of forest management provides guidance on how forest managers set the forest, so that it is ready to be sustainably managed and used. The forest setting is based on the natural properties of forest - bio- physical characteristics, social condition, financial, and economic. In forest management practice, the quite broad science coverage is not fully used (Kartodihardjo 2013). Regulations regarding forest management are determined more only by the forestry physical property basis, as they are contained in the various settings of the silviculture system, forest inventory, as well as forest harvesting, either in natural forest or plantation forest (Kartodihardjo et al. 2006). This practice leds science of forest management become a kind of discourse which does not have a strong relationship with other disciplines such as institutional science and political science. DOI: 10.7226/jtfm.19.3.208